Evaluating Behaviorally Motivated Policy: Experimental Evidence from the Lightbulb Market - Allcott, Hunt; Taubinsky, Dmitry (American Economic Review, 2015)
Imperfect information and inattention to energy costs are important potential motivations for energy efficiency standards and subsidies. We evaluate these motivations in the lightbulb market using a theoretical model and two randomized experiments. We derive welfare effects as functions of reduced-form sufficient statistics capturing economic and psychological parameters, which we estimate using a novel within-subject information disclosure experiment. The main results suggest that moderate subsidies for energy-efficient lightbulbs may increase welfare, but informational and attentional biases alone do not justify a ban on incandescent lightbulbs. Our results and techniques generate broader methodological insights into welfare analysis with misoptimizing consumers. (JEL D12, D83, H21, H31, L67, Q41, Q48)